Chicken soup for the teenage soul : an update of the 1997 classic - Canfield, Jack, 1944-; Hansen, Mark Victor; Kirberger, Kimberly, 1953-; Newmark, Amy (Chicken Soup for the Soul, LLC, 2021)
"Chicken Soup for the Teenage Soul 25th Anniversary Edition has been refreshed and updated with additional, new stories to help today's teens be the happiest, best versions of themselves. The book provides inspiration and advice to help teens grow up and be their best"--